Degenerasi dan nekrosis pada neuron penyusun sistem saraf enterik di usus halus dan usus besar tikus yang diinjeksi paraquat dichloride - Tri Wahyu Pangestiningsih; Daisynta Prima Aninditya; Gerarda Gita Puspitandaru; Iffah Sofana; Rina Pratiwi (Livestock and Animal Research, 2021)
Objective: In Parkinson's disease (PD) patients, there is a disruption in the function of catecholaminergic neurons in Enteric nervous system (SSE) with some symtoms: constipations and diarrhea. Paraquat dichloride (PQ) is a neurotoxic herbicide which is thought to induce PD. This study aims to study the histological features of neurons in the enteric nervous system of small and large intestines injected with PQ.Methods: Ten rats were divided into 2 groups of 5 each. The control group was injected with distilled water and the treatment group was injected with PQ 7 mg/kg BW. The injection was given intraperitoneally, twice a week for 3 weeks with a volume of 1 ml/injection. Small intestine and large intestine were collected and processed for histological preparations in paraffin incisions, then stained with cresyl violet and immunohistochemistry using tyrosine hydroxylase antibody as a marker of catecholaminergic neurons. Intestinal histological preparations were observed under light microscope and analyzed descriptively.Results: Neurons in the small intestine and large intestine of normal group rats were observed normal, while in the treatment group some neurons were normal, but some of them became degeneration in the form of chromatolysis, also necrosis which was characterized by damage of cell membranes, karyolysis, loss of most of the Nissl bodies, and decreased numbers of catecholaminergic neurons.Conclusions: Paraquat dichloride cause changes in enteric nervous system’s neuron structures in the form of degeneration, necrosis, and a decrease in the number of catecholaminergic neurons in the small intestine and large intestine.